Effects of varieties and seasons on cost efficiency in rice farming: A stochastic metafrontier approach - Ho, Phuc Trong; Hung, Pham Xuan; Tien, Nguyen Duc (Asian Journal of Agriculture and Rural Development, 2023)
Rice production costs vary substantially across rice varieties and cropping seasons; however, the effects of rice varieties and cropping seasons on the cost efficiency of rice farming have not been given much attention by researchers. In this paper, we attempt to examine these effects on the cost efficiency of rice production in Vietnam. We use a stochastic metafrontier approach to compare the cost efficiency of rice production between two rice variety groups (a high-quality rice variety and a conventional rice variety group) and three cropping seasons (Winter-Spring, Summer-Autumn, and Autumn-Winter). The data consist of 918 observations collected from rice farmers in the Mekong River Delta, the main rice-cultivation region of Vietnam. The results show that there is statistical evidence for the effects of rice varieties and cropping seasons on cost efficiency. High-quality rice variety adopters performed less efficiently (0.837) than non-adopters (0.864). Rice farmers exhibited a lower mean cost efficiency in the Winter-Spring season (0.883) than in the Summer-Autumn (0.907) and Autumn-Winter (0.905) seasons. This research suggests that policies should support inefficient rice farmers to reduce their inefficiency in the Winter-Spring season as well as support high-quality rice variety adopters to catch up with the cost-efficiency level of conventional rice variety farmers.